2002
DOI: 10.1111/1532-7795.00040
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Patterns of Coping of Inner–City Youth to Psychopathology Symptoms

Abstract: This study provides empirical verification that variations in patterns of coping can explain current and future functioning of youth. The study evaluated the methods and styles of coping of inner–city youth and their relation to age, gender, ethnicity, stress levels, and internalizing and externalizing symptom levels. Three hundred seventy–two 12– to 16–year–old adolescents from inner–city schools (67.0% African American, 24.4% Hispanic; 53.41% males) participated. One hundred forty–nine were also included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 32 publications
13
137
1
Order By: Relevance
“…Second, the convergent validity of the CSQ-CA was supported by the positive relationship with constructs such as internalizing (i.e., anxiety and depression) and externalizing (i.e., acting out) problem behavior, experience of daily hassles, and with maladaptive emotion regulation strategies such as rumination, catastrophizing, self-blame and other-blame. These findings are in line with the results of Tolan et al (2002), who used a social stress measure and found health problems to be related to internalizing and externalizing problem behavior and family transitions to externalizing problems in inner-city youth. Comparatively, self-reported stress predicted increases in rumination 4 months later, which in turn, mediated the relationship between self-reported stress exposure and increases in anxiety over a 7-month period in adolescents (Michl et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Second, the convergent validity of the CSQ-CA was supported by the positive relationship with constructs such as internalizing (i.e., anxiety and depression) and externalizing (i.e., acting out) problem behavior, experience of daily hassles, and with maladaptive emotion regulation strategies such as rumination, catastrophizing, self-blame and other-blame. These findings are in line with the results of Tolan et al (2002), who used a social stress measure and found health problems to be related to internalizing and externalizing problem behavior and family transitions to externalizing problems in inner-city youth. Comparatively, self-reported stress predicted increases in rumination 4 months later, which in turn, mediated the relationship between self-reported stress exposure and increases in anxiety over a 7-month period in adolescents (Michl et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…As discussed previously, this coping factor emphasizes attention redeployment and distractions when stressors are encountered. Consistent with past research (e.g., Tolan et al, 2002), use of coping strategies that distance oneself from the problem is associated with substance use and increased symptomatology (Tolan et al, 2002). Interestingly, use of emotional rumination was associated with less alcohol consumption in African Americans; this coping strategy was maladaptive (i.e., associated with more alcohol consumption) for Whites, as it was in the overall sample (see above).…”
Section: Discussionsupporting
confidence: 82%
“…Coping levels, and the types of coping responses that comprised each level, were determined by the CYDS team based on reviews of theory and empirical findings (e.g., Compas et al, 2001;Tolan et al, 2002) prior to coding of data. Coping responses were assigned to levels without reference to the specific stressors prompting them.…”
Section: Methodsmentioning
confidence: 99%
“…Some research has begun to address these recommendations. For example, Tolan and colleagues examined the longitudinal association between coping with many types of stressors and internalizing and externalizing symptoms among a sample of inner-city minority males (Tolan, Gorman-Smith, Henry, Chung, & Hunt, 2002). Coping "minimally" with stressors (e.g., avoidance of problem solving through substance use, venting emotions) was associated with greater increases in symptoms over 1-year compared with coping through support or seeking guidance from others (e.g., talking things out with parents, low use of venting emotions).…”
Section: Coping As a Moderator Of Riskmentioning
confidence: 99%